Performance Pay and Alcohol Use in Germany - Mehrzad B. Baktash; John S. Heywood; Uwe Jirjahn (Global Labor Organization (GLO), 2021)
We study the link between performance pay and alcohol use in Germany, a country with mandated health insurance. Previous research from the US argues that alcohol use as a form of "self-medication" may be a natural response to the stress and uncertainty of performance pay when many workers do not have access to health insurance. We find that the likelihood of consuming each of four types of alcohol (beer, wine, spirits, and mixed drinks) is higher for those receiving performance pay even controlling for a long list of economic, social and personality characteristics and in sensible IV estimates. We also show that the total number of types of alcohol consumed is larger for those receiving performance pay. We conclude that even in the face of mandated health insurance, the link found in the US persists in Germany.
Keywords: I12; J33; 330; Performance Pay; Alcohol; Stress